DINAMIKA PEMIKIRAN TAFSIR DI INDONESIA: TAFSIR RAHMAT KARYA OEMAR BAKRY - Ramadhan, Kurniadi; Rahman, Pathur; Nasrullah, Muhamad (STAI Asy-Syukriyyah, 2024)
This research discusses Tafsir Rahmat by Oemar Bakry, which aligns with the purpose of the Quran's revelation to be a mercy to the entire universe. The commentary is compiled in a concise format, comprising only one volume, to facilitate readers in obtaining guidance and wisdom from the Quran. The research adopts the method of literary study, using Tafsir Rahmat as the primary source and other works as supporting materials. The findings conclude that Tafsir Rahmat falls into the category of individual commentary, meaning it is authored by one person.